Pengaruh Umur terhadap Kejadian Unmet Need di Provinsi Banten - Rita Ariesta; Deden Gumilang Nugraha (Akademi Kebidanan La Tansa Mashiro, 2020)
Unmet need can be defined as a group whose contraceptive needs have not been met, including all men or women of childbearing age who are married or living together and are considered sexually active who do not use contraceptive methods, either those who do not want to have more children or delay the next birth.Unmet need affects the increase in population which is still one of the most difficult population problems to be resolved in Indonesia. Apart from population density, unmet need also has an impact on health problems. The impact of unmet need for family planning is an increase in maternal mortality (IDHS, 2012). Data from SDKI Banten (2012) found that 74% wanted family planning, where only 64% of family planning needs were met, meaning that 10% of family planning needs had not been met. Developments in the IDHS (2017) actually show a decrease in the number of those wishing to have family planning to fall to 71%, only 62% of family planning needs are met while the unmet family planning needs are still at 10%. (SDKI.2017) This study used a cross-sectional design. The sampling technique used is a saturated sample, where the entire population is used as the research sample. This research is a further analysis using data from the 2017 Indonesian Demographic Health Survey (IDHS) questionnaire for women of childbearing age (WUS) and was conducted during September - December 2019. The results of the study on age have a significant relationship with the incidence of unmet need. With an OR value of 2.8, it means that respondents who are 35 years old have almost 3 times greater risk of experiencing unmet need compared to respondents who are 35 years old. CI 95% (1.721 – 4.572) shows a positive relationship between age and the incidence of unmet need where the older the respondent is, the more likely it is for unmet need to occur. CIE is focused on EFA with at-risk ages ( 35 years) by involving religious leaders where as age increases in our culture, human focus also increases in religious matters so that input from religious leaders is more acceptable.